Citrate-based fluorometric sensor for multi-halide sensing - Dingbowen Wang; Tunan Xia; Yuqi Wang; Yizhu Chen; Chenji Zhang; William Murray; Adam Thomas Schultz; Zhiwen Liu; Jian Yang (Smart Materials in Medicine, 2022)
Halides play important roles in human health and environmental monitoring. However, different halides interfere with each other in current measurement methods. Simultaneous sensing of multiple halides in a fast and low-cost manner remains a challenge. Here, we report a fluorometric multi-halide sensing method by using a single citrate-based fluorophore, CA-Cys, on a custom-made portable device. The fluorescence emitted by CA-Cys is quenched due to the dynamic quenching of halide ions; the sensitivities vary from halide types and pH, providing the capability to obtain multiple Stern-Volmer equations at various pH values. The concentration of each halide can then be obtained by solving the resultant set of equations. A mM scale detection limit is demonstrated, which is suitable for halide wastewater monitoring. A proof-of-concept smartphone-based portable device is also fabricated and tested. The results from the fluorometer and portable device indicated that our multi-halide system is promising for real-world multi-halide sensing applications. This work represents a new direction in developing portable, low-cost, and simultaneous multi-halide sensing technologies.